Facile One‐Pot Synthesis of [1, 2, 3]Triazolo[1, 5‐a]Pyridines from 2‐Acylpyridines by Copper(II)‐Catalyzed Oxidative NN Bond Formation. Issue 14 (25th February 2014) - Hirayama, Tasuku; Ueda, Satoshi; Okada, Takahiro; Tsurue, Norihiko; Okuda, Kensuke; Nagasawa, Hideko
Abstract An efficient and simple method for the synthesis of various [1, 2, 3]triazolo[1, 5‐a]pyridines has been established. The method involves a copper(II)‐catalyzed oxidative NN bond formation that uses atmospheric oxygen as the terminal oxidant following hydrazonation in one pot. The use of ethyl acetate as the solvent dramatically promotes the oxidative NN bond‐formation reaction and enables the application of oxidative cyclization in the efficient one‐pot reaction. A mechanism for the reaction was proposed on the basis of the results of a spectroscopic study.